Time-Inclined Method for High-Fidelity Rotor/Stator Simulations - Miguel Montiel; Roque Corral (Aerospace, 2023)
The application of the time-inclined method in a fourth-order unstructured flux-reconstruction code for turbomachinery is demonstrated. Inviscid and viscous unsteady results due to the interaction of an incoming gust of total pressure with a linear cascade of flat plates and a linear cascade of T106A low-pressure turbine airfoils are reported. The agreement between the time-inclined method and the equivalent full-annulus multipassage solution is very high for both cases. Viscous solutions at Reynolds numbers of <semantics>104</semantics> and <semantics>105</semantics> were conducted. A high degree of matching was obtained between the time-inclined and the whole annulus approaches. The limitations of the method are explored and discussed. While the evolution of the unsteady boundary layers created by the interaction with the incoming wakes was very well captured, the mixing associated with the trailing edge vortex shedding was less accurate. The critical parameter controlling the method’s accuracy is the local Strouhal number. It was demonstrated that the benefit of retaining the exact blade count in the simulations overcomes the slight differences in the mixing due to the limitation of the time-inclined method to model viscous effects accurately in all situations.